Strategy for Improving Rice Agroindustry Production Processes Based on Green Value Stream Mapping - Yulianto, Kiki; Ismanto, Sahadi Didi (Newinera Publisher, 2024)
The rice agroindustry faces challenges due to high inefficiency and negative environmental impacts from excessive resource use. This study aims to improve production processes using Green Value Stream Mapping (GVSM) to reduce non-value-added activities and optimize natural resource usage. The research involves literature review, field observation, interviews, brainstorming, and expert opinions. The production process from seeds to distribution consumes 265 kWh of energy and 8 million liters of water, generates 10,532 kg of waste, and impacts 1.2 hectares of biodiversity. The study confirms that the GVSM strategy enhances operational efficiency and contributes to broader environmental sustainability. The research provides practical guidelines for rice agroindustry companies to implement more environmentally friendly and efficient production practices.